Avtoriteta na področju vzgoje in verovanja v digitalni dobi - Vodičar, Janez (Bogoslovni vestnik, 2023)
Authority is suspect in a democracy. In this article we show what problems this creates in the field of education. Authority is also lost in religion. Religious and educational authority has lost its place, especially in the process of digitalization. The digital environment offers freedom of choice and seemingly democratic use. However, we will show how new forms of authority are also emerging in this environment, which are largely hidden and therefore much more dangerous. The positioning of so-called algorithmic authority leads us to look for appropriate responses for the field of education and proclamation, as it turns out that this is a very similar way of dealing with authority. The approach offered by P. Freire, through the development of a critical consciousness in a concrete environment and the positioning of the teacher as a prophet, combines solutions for the empowerment of modern man in both the religious and educational fields.
Keywords: authority; avtoriteta; digital environment; digitalno okolje; education; faith; oznanjevanje; P. Freire; proclamation; verovanje; vzgoja in izobraževanje